SOCIAL INTERVENTION THROUGH ERGOTHERAPY IN RETIREMENT HOME - Vansač, P. (Україна. Здоров’я нації, 2023)
The aim of our article is to point out the usefulness of ergo-therapy in retirement home. Occupational therapy is a daily meaningful activity for the elderly, as a treatment that enables the elderly to achieve the functionality of life, as a means of strengthening their physical and mental health.